Interculturality on the border of disciplines. Polish language teaching as a means of intercultural education - STANKIEWICZ, KATARZYNA; ŻUREK, ANNA (Wydawnictwo Naukowe UAM, 2012)
The goal of the article is a presentation of the existing and potential relations between Polish language teaching and intercultural education both in the theoretical and practical aspect. The authors present the basic assumptions and goals of intercultural education, paying particular attention to intercultural learning. What follows is a thorough analysis of the presence of the intercultural approach in the theory and practice of the Polish language didactics and its relation to the pedagogy.
Keywords: Polish language teaching; Polish as a foreign language; Intercultural education; Intercultural learning; Intercultural competence